2010
DOI: 10.1007/s00122-010-1399-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Brassica trigenomic allohexaploid (B. carinata × B. rapa) de novo and its stability in subsequent generations

Abstract: Allopolyploidy plays an important role in plant evolution and confers obvious advantages on crop growth and breeding compared to low ploidy levels. The present investigation was aimed at synthesising the first known chromosomally stable hexaploid Brassica with the genome constitution AABBCC. More than 2,000 putative hexaploid plants were obtained through large-scale hybridisation from various combinations of crosses between different cultivars of Brassica carinata (BBCC) and B. rapa (AA). The majority of plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 55 publications
1
76
0
Order By: Relevance
“…SNP data indicated that there was relatively little homeologous recombination across most of the genome, and allele transmission followed patterns consistent with normal Mendelian segregation (Figure 3). This represents an improvement over previously detected meiotic stability in synthetic Brassica types (Song et al 1995;Szadkowski et al 2010;Tian et al 2010;Xiong et al 2011;Zou et al 2011). This effect may be related to the heterozygosity of the initial hexaploid hybrid used in this study (2n = $A j A n B j B c C n C c ), which could facilitate rapid allelic selection for meiotic stability and fertility in resulting progeny.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…SNP data indicated that there was relatively little homeologous recombination across most of the genome, and allele transmission followed patterns consistent with normal Mendelian segregation (Figure 3). This represents an improvement over previously detected meiotic stability in synthetic Brassica types (Song et al 1995;Szadkowski et al 2010;Tian et al 2010;Xiong et al 2011;Zou et al 2011). This effect may be related to the heterozygosity of the initial hexaploid hybrid used in this study (2n = $A j A n B j B c C n C c ), which could facilitate rapid allelic selection for meiotic stability and fertility in resulting progeny.…”
Section: Discussionmentioning
confidence: 64%
“…We found that results from FISH in combination with molecular karyotyping were highly effective for determining detailed chromosome complements in cytogenetically complex hybrids, as has also been demonstrated in oats (Jellen et al 1994), banana, andsugarcane (D'Hont 2005). This analysis highlighted the dangers of using simple chromosome counts to assess meiotic stability of Brassica allohexaploids, as has been done in other studies (e.g., Howard 1942;Tian et al 2010). In the future, molecular karyotyping with molecular cytogenetics may allow identification of genotypic and species-specific variability for meiotic stability in higher-ploidy Brassica.…”
Section: Discussionmentioning
confidence: 81%
“…For MM.AABB and BBCC.MM with higher fertility, advancing generations are needed to establish diploid-like meiotic behavior and improve fertility. Other Brassica allohexaploids involving A, B, and C genomes also suffered from some extents of cytological instability and low fertility (Ge et al 2009;Pradhan et al 2010;Tian et al 2010;Chen et al 2011). Therefore, long time and selection are needed to stabilize these allohexaploids.…”
Section: Discussionmentioning
confidence: 97%
“…Although there are some highly successful hexaploid crops in nature, such as oat, triticale, and bread wheat, no natural allohexaploid species in Brassica are found. However, some efforts were recently made to produce Brassica allohexaploids (AABBCC, 2n = 54) (Ge et al 2009;Pradhan et al 2010;Tian et al 2010;Chen et al 2011). These artificially synthesized allohexaploids can be used as a trigenomic bridge to increase genetic diversity in allopolyploid Brassica crops, or to develop new Brassica species for the future.…”
Section: Introductionmentioning
confidence: 98%
“…Studies on synthetic and naturally occurring recent polyploids suggest that newly formed polyploids may undergo rapid genomic arrangements and chromosomal losses in the first few generations (Shaked et al, 2001;Tian et al, 2010;Matsushita et al, 2012;Chester et al, 2012), which can result in instantaneous loss of several thousand genes from the genome via deletion. Another mode of gene loss is through accumulation of substitutions and/or small indels in the gene body leading to pseudogenization.…”
Section: Pseudogenization Of Duplicate Genesmentioning
confidence: 99%